Respuesta :

Answer:

B. 288 In

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    x*(x-2)-(288)=0

 x • (x - 2) -  288  = 0

Find two factors of  -288  whose sum equals the coefficient of the middle term, which is   -2 .

     -288    +    1    =    -287

     -144    +    2    =    -142

     -96    +    3    =    -93

     -72    +    4    =    -68

     -48    +    6    =    -42

     -36    +    8    =    -28

     -32    +    9    =    -23

     -24    +    12    =    -12

     -18    +    16    =    -2    That's it

Answer: 288